Jammu Mango: New mango variety for sub-tropical region of Jammu and Kashmir - Sharma, Akash; Wali, V K; Singh, V B; Salgotra, Romesh (Indian Horticulture, 2020)
Jammu Mango (Selection-05), a new mango variety developed by Sher-e-Kashmir University of Agricultural Sciences and Technology, Jammu, is suitable for closer spacing under rainfed conditions of sub-tropical region. It is a medium-maturing, semi-vigorous and biennial bearer variety. It is drought hardy, starts flowering in the 3rd week of February with full bloom in first week of March. It has higher fruit set (14.66%) with 446.75 fruits per tree and yields up to 120 kg/tree at the age of 12 years. Fruit skin is smooth, thin and easily separated from the pulp. Flesh is yellow, very tender with a very delicate aromatic flavour. Fruit’s fibre is confined almost entirely to the edge of the seed. The fruits mature and are ready to harvest before the onset of monsoon under sub-tropical conditions of Jammu.